ANALISIS EFISIENSI ENERGI PADA POWER HOUSE DI PT KALIMANTAN PRIMA PERSADA JOBSITE PORT - Firda Herlina; Muhammad Nasyirul Hakim (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
Energy audit is a technique that is used to calculate the amount of energy consumption and identify ways to the savings that includes the inspection activities to determine whether there is a deviation in an activity energy use . The purpose of the study was to determine the condition of the use of energy and look for improving the efficiency of energy use . Consumption energy on 2014 is 1.843.684,49 kWh. From the calculation and analysis shows IKE value on existing buildings diarea work, where there is a value that does not match the standard of which is the IKE BLH with a value of 21.15 kWh / m² / month , BLJ with a value of 19.84 IKE kWh / m² / month , BLK with IKE value of 15.26 kWh / m² / month, and Group Leader Room with IKE value of 37.37 kWh / m² / month. The circuit of the motor there are using star delta on BLH and BLU and soft starter on BLJ and BLK .From these data it can be concluded and carried out repairs on the value IKE by using energy-saving lamps corresponding ISO standard, while the Mega Tower can be done setting the timer on / off with the manual where it is currently night conditions No activity can be reduced coal shipments lighting without prejudice to the rules in the Occupational Health and Safety ( K3 ). And than on non-standard air conditioner can be done replacement AC power in accordance with existing standards and the use of AC technology uses inverter. For the electric motor can still be changed by using a series of soft starter or the inverter to be able to save energy and extend component life. Keywords : energy savings , energy audits , energy efficiency